THE KNOWLEDGE REGARDING PROTEIN ENERGY MALNUTRITION AMONG URBAN AND RURAL MOTHERS WITH UNDER FIVE CHILDREN (International Journal of Food and Nutritional Sciences, 2022)
Malnutrition is one of the leading causes of morbidity and mortality in children aged five years and below malnutrition is a contributing cause in more than half of the children's deaths. Almost half of the deaths worldwide are due to being under weight. Risk factors for severe protein energy malnutrition (PEM) have been identified as ignorance, family size, parents education, poverty, sex of the child and incomplete immunization of the child. The lack of food is not the sole cause of malnutrition. Lack of awareness and knowledge about feeding amount, frequency, type of food etc. contributes significantly to poor nutritional status among children. This study was under taken to assess the knowledge of mothers of under five children regarding prevention of protein-energy malnutrition between urban and rural Area